Vulnerability, Business Resilience, Mechanisms, and Challenges of Village (Barangay) Micro Business Enterprises in the New Normal - Lobaton, John Rey G (Technium Business and Management, 2023)
Micro, small, and medium-sized enterprises (MSMEs) and their employees have been particularly hard hit by the recession because of the COVID-19 pandemic. This study assesses the level of vulnerability and business resilience of two hundred seven (207) Village (Barangay) Micro Business Enterprises (BMBEs) in Bacolod City, Negros Occidental, Philippines. Likewise, it identifies the mechanisms, opportunities, and challenges of BMBEs in the new normal. Respondents of this study are from the wholesale and retail trade and food and beverage service sectors in Bacolod City who were selected using stratified random sampling. The descriptive-comparative research was used in the study and utilized both researcher-made and adapted questionnaires to gather data. Results showed that BMBEs had a moderate level of vulnerability and a high level of business resilience during the COVID-19 crisis. In terms of mechanisms and challenges, most BMBEs adopt technology for promotion purposes and have experienced insufficiency of cash flows to maintain operations. It can be concluded that the businesses were highly resilient during the COVID-19 crisis, as there is only a moderate extent of vulnerabilities from the BMBEs' internal operations. Businesses were able to absorb both internal and external shocks by adjusting to change and seizing opportunities.